Bulgaria School Autonomy and Accountability : SABER Country Report 2014 - World Bank Group (World Bank, Washington, DC, 2015)
In 2011, the World Bank Group commenced a multi-year program designed to support countries in systematically examining and strengthening the performance of their education systems. Part of the World Bank’s new education sector strategy, this evidence based initiative, called saber systems approach for better education results (SABER), is building a toolkit of diagnostics for examining education systems and their component policy domains against global standards, best practices, and in comparison with the policies and practices of countries around the world. By leveraging this global knowledge, the SABER tools fill a gap in the availability of data and evidence on what matters most to improve the quality of education and achievement of better results. This report discusses the results of applying the SABER school autonomy and accountability (SAA) tool in Bulgaria.